To die for : a cookbook of gravestone recipes : food legacies of the people who left behind recipes, etched in stone - Grant, Rosie, 1989- (Harvest, an imprint of William Morrow, 2025)
"A collection of recipes preserved on gravestones, with interviews from the families"-- Provided by publisher.